Exploring LGBT+ campus climate in the UK and Philippines: How prejudice and belonging shape inclusion in higher education. (5th May 2022) - Evangelista, Zyra M.; Lido, Catherine; Swingler, Maxine; Bohan, Jason
Abstract: Although recent global developments suggest progress toward LGBT+ equality, institutional structures perpetuating differential treatment based on sexual orientation and gender identity persist. The present research employed a mixed‐method campus climate study of LGBT+ and cis‐heterosexual students sampled from Higher Education Institutions (HEIs) in the Philippines and the UK. Phase 1 reports a large‐scale survey assessing relationships among students' social attitudes toward LGBT+, campus climate perceptions and experiences of harassment, well‐being, academic persistence, and social identity belonging within the university (LGBT+ = 877; cis‐heterosexual = 2107). Phase 2 reports focus groups and interviews with 35 LGBT+ students, further exploring their campus climate experiences. Triangulated results highlight the role of social identity belonging in creating positive LGBT+ campus climates. Fostering belonging, through visible institutional support for intersectional LGBT+ student organisations and endorsement of LGBT+ inclusive policies and programmes, is recommended for creating safe and inclusive spaces for LGBT+ students.